Healthy eating - Borgert-Spaniol, Megan, 1989- (Minneapolis, MN : Bellwether Media, 2012)
Simple text and photographs discusses what is proper nutrition, including the necessity for eating all five food groups, vitamins, and being active.
Healthy eating with myplate -- The food groups -- Filling your plate -- Exercise -- Feeling great.
Includes bibliographical references (p. 23) and index.
2.6
K-3
510L
Keywords: Nutrition -- Juvenile literature; Health -- Juvenile literature; Nutrition; Health; Readers (Elementary) -- Nonfiction